EDUKASI BUDIDAYA JAMUR TIRAM PADA KELOMPOK WANITA TANI JAMUR TIRAM JAWA GADUT SAIYO LIMAU MANIS KOTA PADANG - Obel, Obel; Yanti , Yulmira; Erona S , Meisilva; Putri , Afrianingsih; Wellyalina, Wellyalina; Ramadhan, Nugraha; Martinsyah, Rachmad Hersi; Fikri, Imam; Wahyudi , Nizar Alim; Munthe, Thomas Syaipuddin; Ananda, Alwi (Universitas Mataram, 2024)
Oyster mushroom cultivation business can provide a variety of very promising benefits both in large scale businesses and small businesses. The demand and selling value is very good in traditional markets and supermarkets. However, white oyster mushroom production is still very low. This is due to several factors such as poor quality seeds, poor marketing strategies and inadequate product processing. For this reason, it is necessary to provide education and assistance in the oyster mushroom business to the Women's Group of Farmers Cultivating Javanese Oyster Mushrooms, Gadut Saiyo Limau Manis, Padang City. The aim of this service activity is to help increase the knowledge and ability to cultivate white oyster mushrooms in the Gadut Saiyo Limau Manis Javanese Oyster Mushroom Farming Women's Group, Padang City. The method used was a lecture and discussion method with members of the Gadut Saiyo Javanese Oyster Mushroom Farming Women's Group. The results of the activity are socialization activities by providing good knowledge of oyster mushroom cultivation. In socialization activities, questionnaires are filled out at the beginning and end of the activity to measure participants' knowledge. The activities carried out received good appreciation and other follow-up activities need to be carried out. Based on the results of the activity, it can be concluded that after the educational activities were carried out there was an increase in the knowledge of the members of the Gadut Saiyo Java Oyster Mushroom Farming Women's Group by 90.48% with a participant satisfaction level of 84% and 90% of participants stated that the activities that had been carried out were very beneficial for members of the Oyster Mushroom Farming Women's Group. Jawa Gadut Limau Manis Padang City.